Ras GTPase-like protein MglA, a controller of bacterial social-motility in Myxobacteria, has evolved to control bacterial predation by Bdellovibrio - Milner, David S.; Till, Rob; Cadby, Ian; Lovering, Andrew L.; Basford, Sarah M.; Saxon, Emma B.; Liddell, Susan; Williams, Laura E.; Sockett, R. Elizabeth (Public Library of Science, 2014)
Bdellovibrio bacteriovorus invade Gram-negative bacteria in a predatory process requiring Type IV pili (T4P) at a single invasive pole, and also glide on surfaces to locate prey. Ras-like G-protein MglA, working with MglB and RomR in the deltaproteobacterium Myxococcus xanthus, regulates adventurous gliding and T4P-mediated social motility at both M. xanthus cell poles. Our bioinformatic analyses suggested that the GTPase activating protein (GAP)-encoding gene mglB was lost in Bdellovibrio, but critical residues for MglABd GTP-binding are conserved. Deletion of mglABd abolished prey-invasion, but not gliding, and reduced T4P formation. MglABd interacted with a previously uncharacterised tetratricopeptide repeat (TPR) domain protein Bd2492, which we show localises at the single invasive pole and is required for predation. Bd2492 and RomR also interacted with cyclic-di-GMP-binding receptor CdgA, required for rapid prey-invasion. Bd2492, RomRBd and CdgA localize to the invasive pole and may facilitate MglA-docking. Bd2492 was encoded from an operon encoding a TamAB-like secretion system. The TamA protein and RomR were found, by gene deletion tests, to be essential for viability in both predatory and non-predatory modes. Control proteins, which regulate bipolar T4P-mediated social motility in swarming groups of deltaproteobacteria, have adapted in evolution to regulate the anti-social process of unipolar prey-invasion in the “lone-hunter” Bdellovibrio. Thus GTP-binding proteins and cyclic-di-GMP inputs combine at a regulatory hub, turning on prey-invasion and allowing invasion and killing of bacterial pathogens and consequent predatory growth of Bdellovibrio.